Discrete event modeling for operational management of restaurants - Caballero Salazar, Marcelo Alonso (2023)
Models are a tool that allow us to simulate real life systems in a virtual environment to generate scenarios and observe how the system reacts. Restaurant management systems incorporate the concepts of RevPash and Menu Analysis to support difficult decisions in pricing, promotions and resource management. In this paper, using Arena 14.0 software, a discrete event model was designed that incorporates the above concepts and simulates the operations of a restaurant. Based on the proposed model, measures were proposed to improve the restaurant's profitability and scenarios were designed with the possible effects. The value of this proposal lies in the economic advantage that can be obtained with the application of models and Menu Analysis in restaurant management.